Comparative Semantic Analysis of Business Discourse in the English and Uzbek Languages - Tursunova, Mashkhura (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This article explores the semantic features of business discourse, focusing on how meaning is constructed and interpreted in professional communication. Key lexical units, terminologies, and collocations are analyzed with examples from English and Uzbek business texts. The study highlights the role of semantic clarity and cultural context in achieving effective communication in business settings.